Determinants of corruption in Asia Pacific / Nurulaisyah Mohamad Nor - Mohamad Nor, Nurulaisyah (2018)
Corruption seem to be the severe problem that can hinders the development in a country. The purpose of this research is to investigate the determinants of Corruption in Asia Pacific country. The determinants that were examined are Gross Domestic Product, Unemployment, economic freedom, political stability and inflation. The data were used in this study was secondary data and were collected from Transparency International, World Development indicator (WDI) and DataStream. This study used a panel data in yearly basis from 2010 to 2016 which is seven interval time as to examine the causality. The panel linear regression were used in this study as to examined the relationship between (GDP, Unemployment, economic freedom, political stability and inflation) towards corruption. As this research papers identify the component that can affect to corruption as to implement new initiative to combat corruption.